New benzyl-aporphine alkaloids from Thalictrum cultratum. Issue 21 (2nd November 2019) - Kang, Wenjia; Li, Jianyong; Li, Dahong; Li, Zhanlin; Chen, Shengshuang; Hua, Huiming; Bai, Jiao
Abstract: Two new rare benzyl-aporphine alkaloids, thaliculine (1 ) and 6a, 7-dehydrothaliculine (2 ), were isolated from the roots of Thalictrum cultratum Wall. Their structures were determined based on spectroscopic analysis including 1D, 2D NMR, and HR-ESI-MS. The stereochemistry of1 was assigned by ECD spectroscopy. Compound1 exhibited weak cytotoxicity against HL-60 cell line with IC50 value of 31.40 μM. Abstract :